Constitutional interpretation the basic questions - Barber, Sotirios A.; Fleming, James E. (Oxford : New York ; Oxford University Press, 2007)
Ronald Dworkin famously argued that fidelity in interpreting the Constitution as written calls for a fusion of constitutional law and moral philosophy. Barber and Fleming take up that call, arguing for a philosophic approach to constitutional interpretation.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Constitutional law -- United States